The Impact of Demographic and Economic Change on the Australian Generational Economy: Financial Sustainability, Intergenerational Inequality, and Material Living Standards - Rice, James Mahmud; Wilson, Tom; Temple, Jeromey B.; McDonald, Peter (Frontiers in Public Health, 2022)
The generational economy—which is that aspect of the economy that pertains to the economic activities of, and the economic relationships between, different ages and generations—can be evaluated on the basis of a number of different criteria. The most critical of these include the financial sustainability of the generational economy, the intergenerational inequality that the generational economy creates, and the material living standards associated with the generational economy. How the generational economy performs in terms of these three criteria is, moreover, shaped by underlying processes of demographic and economic change. This paper examines how the Australian generational economy can be expected to perform in coming decades in terms of financial sustainability, intergenerational inequality, and material living standards. How the performance of the Australian generational economy is shaped by variations in fertility, mortality, overseas migration, and labour-income growth is also assessed. The results reported in the paper indicate that, because of population aging, consumption can only grow at a substantially lower rate than labour income if financial sustainability is to be maintained. These results also suggest that increasing overseas migration is a distinctly useful policy tool for meeting the challenges posed by population aging, since increasing overseas migration both increases material living standards and decreases intergenerational inequality.